The insight discipline : crafting marketplace understanding that makes a difference - Fahey, Liam, 1951- (AMA leadership series, 2020)
In his re-published book The Insight Discipline, Liam Fahey details the analysis methods and modes of deliberations required to overcome the insight challenge and to create an insight-driven culture. He lays out the business case for why leaders must emphasize the goal of attaining new insight if they want to gain maximum value from analysis.